Partisipasi Perempuan dalam Pengelolaan Usaha Garam - Faizah Khotimatul Husna; Arie Rachma Putri (Universitas Muhammadiyah Klaten, 2026)
Currently, the economic sector—especially small and micro enterprises—plays an important role in Indonesia’s economic growth. MSMEs (Micro, Small, and Medium Enterprises) have shown resilience during economic crises. In managing these businesses, women significantly contribute to their development. Their participation in entrepreneurship has a positive impact on the socioeconomic status of families. In Rembang Regency, one key economic activity is the processing of marine products, including salt, with women supporting these enterprises. This research aims to examine women’s involvement in managing salt businesses. The findings show that women’s participation, such as attending meetings organized by cooperatives or groups, is generally less frequent than that of men. More than half of women surveyed reported never or rarely joining group activities. Additionally, women are less likely to give suggestions, with two-thirds of respondents indicating low involvement in decision-making. The main challenge faced by women in this sector is a lack of ideas for proposals. Other obstacles include hesitation to express opinions and a tendency to follow existing group decisions. Overall, while women play an essential role in supporting salt business development, their direct participation in formal activities and decision-making processes remains limited. Encouraging more active involvement could further improve business outcomes.